Engaging the senses in the Tibetan tantric 'major practice session' (sgrub chen) - Cantwell, C (Lumbini International Research Institute, Nepal, 2019)
It is well-known that tantric Buddhism takes a different approach towards sensual pleasures than mainstream Buddhism. While accepting the analysis of the problematic attachment and aversion resulting from indulgence in sensual gratification, the tantric spiritual discipline involves enlisting bodily experiences, and transforming ordinary body, speech and mind into their enlightened counterparts. The ways in which the senses are used in a "Major Practice Session", a communal ritual lasting for some ten days or so, is explored in this chapter. In such a practice session, the meditations and ritualised performances are led by the principal lama and his team of expert meditators and ritualists, while the larger assembly need not necessarily actively join in. It is enough if they sit receptively and engage their senses - watching the performance, listening to the chanting and music, smelling the incense, touching the ritual implements, and tasting the consecrated pills. Thus, they can develop the "pure vision" of the world as an enlightened "mandala". The emphasis on sensual experience rather than on expressions of belief, or active congregational participation in the liturgy, means that attendance is relatively open, with Buddhists of other schools, and non-Buddhists, able to participate.